Upaya Pemberdayaan Wirausaha Disabilitas Fisik - Rizki Ardi Arrahman; Prantasi Harmi Tjahjanti; Abdi Chandra Putra (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Community Service (Abdimas) this paper presents empowerment efforts for physical disabilities in the independent age category where they have their own entrepreneurs. There are 15 people who live in Surabaya and Sidoarjo, with the same problem, namely to improve their entrepreneurship. The first is the empowerment effort by providing a business capital loan of one million rupiah which will be returned five times. The form of the loan does not use interest, so it is not usurious, the second is taking care of the legality of their entrepreneurship, namely the Business Identification Number (NIB) for free, so that their entrepreneur is licensed/legally, and the third is giving donations in the form of basic necessities. All of this assistance is evaluated for three months to see the results. The results obtained from capital loans provide continuity of their entrepreneurship, although not high, the value of income from their business has increased by up to 15%. Meanwhile, the NIB they received was a 'weapon' as a license to do business. Meanwhile, basic food assistance can help their lives with the current condition of rising prices.